A New Approach to Human Society Development in Global World - Buzni, A.M. (Економічний вісник Донбасу, 2013)
The threats to the survival of civilization and life on Earth in market economy conditions were under consideration and the approach to the development of the international community on the basis of change in consumer consciousness to spiritual one made in Vernadsky’s work on noosphere is justified. The author proposes to implement the Vernadsky’s idea about scientists’ International establishing and, in particular, the creation of an international institute of scientists to develop a model of the ideal society. Розглянуто погрози існування цивілізації і життя на Землі в умовах ринкової економіки й обґрунтовується підхід до розвитку світового співтовариства на основі заміни споживчої свідомості духовною, висловленій в навчанні В. І. Вернадського про ноосферу. Автор Пропону реалізувати ідею В. І. Вернадського про інтернаціонал вчених і, зокрема, створення міжнародного інституту вчених для розробки моделі ідеального суспільства. Рассмотрены угрозы существования цивилизации и жизни на Земле в условиях рыночной экономики и обосновывается подход к развитию мирового сообщества на основе замены потребительского сознания духовным, высказанном в учении В. И. Вернадского о ноосфере. Автор предлагает реализовать идею В. И. Вернадского об интернационале учёных и, в частности, создание международного института учёных для разработки модели идеального общества.